2014
DOI: 10.1007/s00704-014-1297-6
|View full text |Cite
|
Sign up to set email alerts
|

Plausible influence of Atlantic Ocean SST anomalies on winter haze in China

Abstract: The possible influence of Atlantic sea surface temperature (SST) on winter haze days in China at interannual and decadal time scales is investigated using the observed haze-day data from 329 meteorological stations, National Centers for Environmental Prediction-National Centers for Atmospheric Research (NCEP-NCAR) reanalysis, and a SST dataset for 1978-2012. Wintertime haze days in China show robust interannual variations and significant increases over time. The SST anomalies over the North Atlantic from summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…S1b). The trend pattern of wintertime HD is consistent with the observational results examined by previous studies1120. The associated principal component (PC) (blue line in Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…S1b). The trend pattern of wintertime HD is consistent with the observational results examined by previous studies1120. The associated principal component (PC) (blue line in Fig.…”
Section: Resultssupporting
confidence: 90%
“…The HD increasing trend over eastern China is highly correlated with the weakening of surface wind speed14 and decreasing trend of atmospheric relative humidity11. Several studies have suggested that the interannual variability of winter haze over China may be affected by the East Asian winter monsoon19 and the sea surface temperature (SST) in Atlantic Ocean20.…”
mentioning
confidence: 99%
“…Therefore, we conclude that the major forcing factor of atmospheric loading of pollutants and the resulting haze days in China was wind strength rather than anthropogenic emissions. This conclusion is consistent with the coincidence of the haze days with weak wind strength observed in the meteorological registers of the past several decades (H Chen & Wang, ; Hui & Xiang, ; H Wang et al, ; Xiao et al, ). Nevertheless, the dominant role of wind strength cannot exclude the contribution of anthropogenic emissions to high exposure to aerosol pollutions in China.…”
Section: Resultssupporting
confidence: 87%
“…To discriminate the major forcing factors of wind strength over the past 180 years, we compared our records with the observed temperature changes in China (Shaowu et al, ), the annual average tropical ocean surface temperature (TSST; Huang et al, ), the Atlantic Multidecadal Oscillation (AMO; Trenberth & Shea, ), and the Arctic sea ice extent (ICE; H Wang et al, ; Figure ). All these factors have been suggested as the major forcing factors of heavy haze days in China (Hui & Xiang, ; H Wang et al, ; Xiao et al, ). Notably, the wind strength is inversely related to the meteorological registers of temperature changes in China, suggesting a close association between them (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…When the pre-autumn SST anomalies were distributed in a "+ − +" pattern from south to north, the subsequent EAWM was stronger, and the surface temperature of north China was lower (Shi, 2014). Xiao et al (2015) proved the SST anomalies over the North Atlantic from summer to the following winter exhibit a significant relationship with winter haze days on both decadal and interannual timescale. Similarly, the CC between WHD NCP DY and pre-autumn SST DY of the Atlantic was distributed in a "− + −" pattern (Fig.…”
Section: The Predictors and Associated Circulationsmentioning
confidence: 95%